1994
DOI: 10.1161/01.cir.90.6.2870
|View full text |Cite
|
Sign up to set email alerts
|

Relation between physical training and ambulatory blood pressure in stage I hypertensive subjects. Results of the HARVEST Trial. Hypertension and Ambulatory Recording Venetia Study.

Abstract: These data suggest that participation in aerobic sports may attenuate the risk of hypertension in young subjects whose office BP is in the stage I hypertensive range at office measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 32 publications
3
115
0
Order By: Relevance
“…Several population studies have indicated that increased physical activity is inversely proportional to cardiovascular mortality in the long term. The practice of moderately intense physical activity reduces the future risk of presenting HBP and its progression, resulting in a favorable effect in reducing early mortality (19,20). Of the 45 hypertensive patients who took part in this study, only 7 (15.5%) practiced some form of physical activity (we recommend regular aerobic exercise, like brisk walking, at least half an hour a day, almost everyday of the week) (4).…”
Section: Discussionmentioning
confidence: 99%
“…Several population studies have indicated that increased physical activity is inversely proportional to cardiovascular mortality in the long term. The practice of moderately intense physical activity reduces the future risk of presenting HBP and its progression, resulting in a favorable effect in reducing early mortality (19,20). Of the 45 hypertensive patients who took part in this study, only 7 (15.5%) practiced some form of physical activity (we recommend regular aerobic exercise, like brisk walking, at least half an hour a day, almost everyday of the week) (4).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Only subjects who had at least 6 months of follow-up were included. Patients' recruitment was obtained with the collaboration of the local general practitioners who were instructed during local meetings.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline data included a medical and family history and a selfcompiled questionnaire about lifestyle habits: current use of coffee and alcoholic beverages, smoking status, and physical activity habits. [11][12][13] Other details are reported in the online-only Data Supplement. Brachial office BP at entry was the mean of 6 measurements obtained with a mercury sphygmomanometer with appropriately sized cuffs, during 2 visits performed 2 weeks apart.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 However, it is still debated whether the sympathetically mediated beneficial effect of physical activity on arterial compliance, particularly small artery compliance, is merely due to the reduction of heart rate and BP or to a direct effect on the arterial wall. 9,[15][16][17][18][19] Regular physical activity, through a reduction of sympathetic activity, may lead to a reduction of smooth muscle tone thereby decreasing the stiffness of the muscular arteries. Increased sympathetic tone is frequently associated with hypertension in young-to-middle-age adults 20 and thus a non-pharmacological measure that reduces the sympathetic tone could have beneficial effects on the small artery elasticity of these subjects.…”
Section: Introductionmentioning
confidence: 99%